Simulation of Uniformly Distributed Vibration Effects on a Reciprocal Fiber-optic Polarimetric Current Sensors - Tantaswadi, P.; Tangtrongbenchasil, C. (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
Mechanical vibration affects the accuracy of optical fiber current sensor causing error in optical current measurement. In practice, the sensing part of the optical sensor is susceptible to environmental perturbations such as mechanical vibration to the sensing fiber. Reciprocal polari-metric sensor configuration can reduce current measurement error due to the vibration. The accuracy of our model is within 0.01% of the actual value and satisfies application in metering. Keywords: fiber optic current sensor, uniformly distributed vibration effect, polarimetric current sensor. Corresponding author: E-mail: cast@kmitl.ac.th